Characterization of a family of gamma-ray-induced CHO mutants demonstrates that the ldlA locus is diploid and encodes the low-density lipoprotein receptor. - Sege, R D (1986)
The ldlA locus is one of four Chinese hamster ovary (CHO) cell loci which are known to be required for the synthesis of functional low-density lipoprotein (LDL) receptors. Previous studies have suggested that the ldlA locus is diploid and encodes the LDL receptor. To confirm this assignment, we have isolated a partial genomic clone of the Chinese hamster LDL receptor gene and used this and other nucleic acid and antibody probes to study a family of ldlA mutants isolated after gamma-irradiation. Our analysis suggests that there are two LDL receptor alleles in wild-type CHO cells. Each of the three mutants isolated after gamma-irradiation had detectable deletions affecting one of the two LDL receptor alleles. One of the mutants also had a disruption of the remaining allele, resulting in the synthesis of an abnormal receptor precursor which was not subject to Golgi-associated posttranslational glycoprotein processing. The correlation of changes in the expression, structure, and function of LDL receptors with deletions in the LDL receptor genes in these mutants directly demonstrated that the ldlA locus in CHO cells is diploid and encodes the LDL receptor. In addition, our analysis suggests that CHO cells in culture may contain a partial LDL receptor pseudogene.